Seagrass under siege? Investigating the effects of microplastics on Eelgrass (Zostera muelleri) in a laboratory-controlled mesocosm study - Jack Greenshields; David J. Beale; Andrew Bissett; Amie Anastasi; Andrew D. Irving; Elizabeth Andrews; Angela Capper (Environmental Pollution, 2026)

Correction to: Harvesting Asparagopsis: understanding regrowth and associated community dynamics - Najeen Arabelle Rula; Angela Capper; Adam Smith; Robert D. Kinley; Manoj Kumar; Emma L. Jackson (Journal of Applied Phycology, 2026)

Characteristics of benthic toxic dinoflagellate communities within three coastal regions of the Great Barrier Reef, Australia - Joseph C. Perkins; Kyall R. Zenger; Angela Capper; Yang Liu; Jan M. Strugnell (Marine Pollution Bulletin, 2026)

Harvesting Asparagopsis: understanding regrowth and associated community dynamics - Najeen Arabelle Rula; Angela Capper; Adam Smith; Robert D. Kinley; Manoj Kumar; Emma L. Jackson (Journal of Applied Phycology, 2026)
The red seaweed Asparagopsis taxiformis can reduce methane emissions in livestock by over 90%, but its mariculture remains in its infancy and biomass for research and commercial use relies partly on wild populations. Knowledge on the impacts of harvesting A. taxiformis is lacking, emphasising the need for ecological research to guide the development of its sustainable harvesting. This study examined the regrowth potential of A. taxiformis meadows following small-scale harvesting. A harvest experiment testing the methods, handpicking and cutting, was conducted in Gladstone, Queensland, Australia, during the austral winter, with plots monitored over six months. Harvesting immediately affected percent cover and shoot length. Handpicked and cut plots exhibited regrowth within four to five months in terms of cover, which notably exceeded or were slightly above that of control plots. The shoot length of harvested plots paralleled that of control plots and was mainly influenced by seasonality. Control plots exhibited reduced growth at three months, suggesting that harvesting mimicked the seasonal reduction in biomass after the winter peak. This study also demonstrated the importance of vegetative propagation in the regrowth of A. taxiformis . The sessile benthic community in harvested plots underwent temporal shifts similar to those in the control plots, indicating that harvesting did not substantially alter community dynamics. Approximately 19 taxa of mobile fauna were recorded within Asparagopsis meadows, potentially indicating its habitat role. Overall, these findings provide ecological insights into the harvesting impacts on this seaweed, with further studies needed to assess broad-scale and long-term impacts.

Taxonomy, distribution, and habitat associations of Gambierdiscus from coastal waters off Queensland, Australia - Joseph C. Perkins; Kyall R. Zenger; Angela Capper; Yang Liu; Jan M. Strugnell (Harmful Algae, 2025)

Selecting optimal substrates for ocean-based cultivation of the red seaweed Asparagopsis taxiformis (Rhodophyta, Bonnemaisoniales) - Emma J. Theobald; Margaret B. Rule; Angela Capper; Guillermo Diaz-Pulido; Emma L. Jackson (Journal of Applied Phycology, 2025)
The red seaweed Asparagopsis taxiformis has the potential to reduce methane emissions from livestock, but key challenges remain in developing scalable, ocean-based cultivation protocols using a closed-lifecycle approach. A critical milestone in this effort is developing seeding methodologies and identifying effective substrates for the attachment of gametophyte germlings. This study evaluates the suitability of synthetic and natural twine substrates and a sodium alginate binder for A. taxiformis germling cultivation under laboratory conditions. Polypropylene, nylon, cotton and sisal twines and a smooth polypropylene control surface were seeded with a germling solution, either directly or within a sodium alginate binder. Germling cover (%) was assessed after six weeks of tank-based cultivation and again following unravelling and exposure to moderate-velocity flow to simulate ocean deployment conditions. Polypropylene twine retained the highest germling cover (104% cover post-exposure), while cotton twine (70% cover) showed promise as a biodegradable alternative. Reduced germling cover was observed on the sodium alginate binder treatments across the majority of substrates, with germling loss particularly high (81% reduction in cover) on the smooth surface of the polypropylene control. By demonstrating a scalable seeding methodology and identifying two effective, widely available substrates for cultivation; polypropylene and cotton twine, this study provides a foundation for developing seeded twine for A. taxiformis mariculture. Field trials will be essential to validate this nursery-stage performance at-sea. Ultimately, optimising seeding techniques and cultivation substrates will be key to scaling A. taxiformis mariculture and unlocking its potential for sustainable bioproduct applications.

Sediment composition influences microplastic trapping in seagrass meadows - Jack Greenshields; Andrew D. Irving; Amie Anastasi; Angela Capper (Environmental Pollution, 2025)

A systematic review to assess current surface water and sediment microplastic sampling practices in seagrass and mangrove ecosystems - Jack Greenshields; Amie Anastasi; Andrew D. Irving; Angela Capper (Environmental Science and Pollution Research, 2024)
Global plastic production is estimated to be 400 million tonnes per annum, with ~ 5.25 trillion fragments floating in our oceans. Microplastics (< 5 mm) have the potential to disproportionately accumulate and become trapped in mangroves and seagrass meadows, creating plastic ‘sinks’. This is concerning as these ecosystems are of great ecological and economic importance, with microplastics causing harm to inhabiting flora and fauna. However, accurately measuring microplastic abundance, comparing findings, and determining potential impacts are difficult due to a lack of standardised sampling protocols. Therefore, a systematic literature review was completed to review currently adopted microplastic sampling methods in surface water and sediment in seagrass and mangrove ecosystems. These were compared with recommendations from existing governmental and institutional groups as a first step to standardising methods for future sampling procedures in seagrasses and mangroves.

Selection of marine macroalgae for nutrient biofilter and bioproduct trials in the coastal waters of Queensland, Australia - Emma J. Theobald; Andrew D. Irving; Angela Capper; Joana F. Costa; Guillermo Diaz-Pulido; Elizabeth L. Andrews; Jo Kelly; Emma L. Jackson (Aquaculture International, 2024)
The capacity of many macroalgae to rapidly absorb soluble inorganic nutrients and convert them into primary biomass provides opportunities for their use in the bioremediation of nutrient-enriched waters. Marine-based macroalgal cultivation has the potential to target diffuse source nutrient discharges and produce valuable bioproducts such as fertiliser, soil conditioning agents and agricultural feed additives and phycocolloids. Whilst macroalgal diversity offers benefits for improving and maintaining healthy marine ecosystems, it also presents a challenge for determining the best candidate species for cultivation as a nutrient biofilter and, ultimately, a source of bioproducts. We developed and applied a multi-criteria selection model to identify likely candidate macroalgal species for cultivation in Queensland’s coastal waters for biofiltration and bioproduct development, focusing on native species and product development for the agronomical and horticultural sectors. From a species database of 1380 macroalgal species, candidates were initially selected based on their regional abundance, distribution and morphological characteristics considered amenable to in-situ cultivation and harvesting. From a resulting shortlist of 17 species, five systematic literature searches were applied to identify biofilter potential, bioproduct potential and current cultivation status. Of the shortlisted species, Ulva lactuca , Gracilaria edulis and Hypnea cervicornis ranked most highly in the multi-criteria analysis, with several other species showing good potential, but requiring further investment in understanding key biological processes and the development of cultivation protocols.

Electro-flocculation of aquaculture wastewater microalgal communities reduces nutrient loading - Angela Capper; Sanath Alahakoon; Christopher Aiken; Rafaela Nunes; Shaneel Chandra; Steven Moore (Bioresource Technology, 2024)

Sequestration and Cyanobacterial Diet Preferences in the Opisthobranch Molluscs Dolabrifera nicaraguana and Stylocheilus rickettsi - Kasey E. Clark; Angela Capper; Wei-Ting Liu; Amanda M. Fenner; Alejandro Almanza; Gina Della Togna; Liuris Herrera; Timothy Johns; Valerie J. Paul; Pieter C. Dorrestein; Todd L. Capson; Marcy J. Balunas (Frontiers in Marine Science, 2021)
A multidisciplinary approach was used to assess chemical ecological dietary interactions between marine organisms as a tool to isolate novel ecologically relevant compounds with biotechnological potential. First, laboratory-based feeding preference assays of the sea hare Dolabrifera nicaraguana (previously known as D. dolabrifera ), an anaspidean mollusc, were conducted by simultaneously offering six food options collected from nearby tidal pools in the Coiba National Park in the Tropical Eastern Pacific of Panama. An evaluation of preferred dietary repertoire revealed D. nicaraguana significantly preferred cf. Lyngbya sp. over the cyanobacterium Symploca sp., green alga Chaetomorpha sp., and red alga Spyridia sp. A no-choice feeding assay using cf. Lyngbya sp. or green alga Cladophora sp. supported this finding. Secondly, we conducted bioactivity-guided fractionation using the preferred food source of D. nicaraguana , the ‘hair-like” cf. Lyngbya sp. from which we also isolated and elucidated two new depsipeptide compounds, veraguamide M ( 1 ) and veraguamide N ( 2 ). Veraguamides M ( 1 ) and N ( 2 ) showed in vitro activity toward the malaria-causing parasite Plasmodium falciparum with GI 50 values of 4.2 and 4.3 μM, respectively, and therapeutic windows of 7.0–8.0 (based on moderate cytotoxicities to mammalian Vero cells with GI 50 values of 29.3 and 34.1 μM, respectively). Veraguamide N ( 2 ) was also active against Leishmania donovani , the causative agent of visceral leishmaniasis, with a GI 50 value of 6.9 μM. We then evaluated sequestration of these new compounds by D. nicaraguana used in the feeding assays and found trace amounts of the dietary sequestered compounds. Finally, we evaluated sequestration of these new compounds by the sea hare Stylocheilus rickettsi (previously known as S. striatus ) that were grazing on the cf. Lyngbya sp. used in the feeding assays and found both to be sequestered. This study is the first example whereby compounds with significant activity against tropical parasites have been found in both the sea hare S. rickettsi and its cyanobacterial food source. These results suggest that chemical ecological studies involving sea hares and cyanobacteria continue to provide a diverse source of bioactive compounds with biotechnological potential.

Chemical Deterrence of a Marine Cyanobacterium against Sympatric and Non-sympatric Consumers - Angela Capper; Edwin Cruz-Rivera; Valerie J. Paul; Ian R. Tibbetts (Hydrobiologia, 2006)

The Fate of Lyngbya majuscula Toxins in Three Potential Consumers - Angela Capper; Ian R. Tibbetts; Judith M. O’Neil; Glendon R. Shaw (Journal of Chemical Ecology, 2005)